A participação do negro em São Luiz Gonzaga-RS: trajetórias e memórias do Clube Recreativo Imperatriz - Morais, Marisete de Mattos (2019)
This study constitutes an investigation into important Afro-Brazilian material and immaterial patrimony almost unknown in the official history of São Luiz Gonzaga-RS: the Literary and Recreative Club Imperatriz, founded in 1943, destined to the black community and years later to the others popular in the municipality and region. From the centrality of the theme, the objective is to investigate through memory, the trajectory of some black families and cultural, political and social aspects that involved the foundation and maintenance of the club. It also seeks to insert the Literary and Recreational Club Imperatriz in the register of Black Clubs of Rio Grande do Sul. To achieve its objectives, it uses concepts and stories of black social clubs, as well as a trajectory of Africans in Brazil, Rio Grande the South and the Region of the Missions, in addition to approaching conceptions of memory in line with Oral History and heritage. The research uses interviews that reconstruct the daily life of the club, its emergence and other important events, which will be used together with the sources official documents such as minutes, statute, municipal laws, books, posture codes, among others. Thus, we seek to investigate elements that prove the experiences as a place of leisure and cultural resistance, identifying attractions such as: library, participation in street carnivals and various festivities. It is also intended to contribute to the process of visibility of the Afro-Brazilians of the municipality and, for the reinterpretation of the local-regional history itself